2021
DOI: 10.5194/wcd-2-71-2021
|View full text |Cite
|
Sign up to set email alerts
|

Extreme wet seasons – their definition and relationship with synoptic-scale weather systems

Abstract: Abstract. An extreme aggregation of precipitation on the seasonal timescale, leading to a so-called extreme wet season, can have substantial environmental and socio-economic impacts. This study has a twofold aim: first to identify and statistically characterize extreme wet seasons around the globe and second to elucidate their relationship with specific weather systems. Extreme wet seasons are defined independently at every grid point of ERA-Interim reanalyses as the consecutive 90 d period with the highest ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…The potential effects of individual HPEs are specifically important in drylands. Recently, in a global analysis of extreme rain seasons, Flaounas et al (2021) showed that while extreme seasons in the arid parts of the globe exhibit much more precipitation than typical years (far more than in other climates), these seasons result from the addition of only a few rain days. Such rain days are exactly the HPEs we explored here, which further emphasise the importance of analysing their relationship with synoptic-scale systems.…”
Section: Heavy Precipitation Events Where There Is Almost No Rainfallmentioning
confidence: 99%
“…The potential effects of individual HPEs are specifically important in drylands. Recently, in a global analysis of extreme rain seasons, Flaounas et al (2021) showed that while extreme seasons in the arid parts of the globe exhibit much more precipitation than typical years (far more than in other climates), these seasons result from the addition of only a few rain days. Such rain days are exactly the HPEs we explored here, which further emphasise the importance of analysing their relationship with synoptic-scale systems.…”
Section: Heavy Precipitation Events Where There Is Almost No Rainfallmentioning
confidence: 99%